Isolated gestational proteinuria preceding the diagnosis of preeclampsia – an observational study. (23rd May 2016) - Yamada, Takahiro; Obata‐Yasuoka, Mana; Hamada, Hiromi; Baba, Yosuke; Ohkuchi, Akihide; Yasuda, Shun; Kawabata, Kosuke; Minakawa, Shiori; Hirai, Chihiro; Kusaka, Hideto; Murabayashi, Nao; Inde, Yusuke; et al.
Abstract: Introduction: Some pregnant women develop significant proteinuria in the absence of hypertension. However, clinical significance of isolated gestational proteinuria (IGP) is not well understood. This study aimed to determine the prevalence of IGP in singleton pregnancies and the proportion of women with IGP who subsequently developed preeclampsia (IGP‐PE) among all PE cases. Material and methods: This was an observational study of 6819 women with singleton pregnancies at 12 centers, including 938 women with at least once determination of protein‐to‐creatinine ratio (P/Cr). Significant proteinuria in pregnancy (SPIP) was defined as P/Cr (mg/mg) level >0.27. IGP was defined as SPIP in the absence of hypertension. Gestational hypertension (GH) preceding preeclampsia (GH‐PE) was defined as preeclampsia (PE) in which GH preceded SPIP. Simultaneous PE (S‐PE) was defined as PE in which both SPIP and hypertension occurred simultaneously. Results: IGP and PE were diagnosed in 130 (1.9%) and 158 (2.3%) of 6819 women, respectively. Of 130 women with IGP, 32 (25%) progressed to PE and accounted for 20% of all women with PE. Hence, women with IGP had a relative risk of 13.1 (95% CI; 9.2–18.5) for developing PE compared with those without IGP [25% (32/130) vs. 1.9% (126/6689)]. At diagnosis of SPIP, P/Cr levels already exceeded 1.0 more often in women with S‐PE than in those with IGP‐PE [67% (33/49) vs. 44% (14/32), respectively, p = 0.031]. Conclusions: IGP is a risk factor for PE, and IGP‐PE accounts for a considerable proportion (20%) of all PE.